GREEN ALLOY OF SILVER NANOPARTICLES FROM ENDOPHYTIC EXTRACTS OF WITHANIA SOMNIFERA AND STUDIES OF ANTIBACTERIAL AND ANTIMITOTIC ACTIVITY - B, Hemashekhar; M, Govindappa; Ganganagappa, Nagaraju; N, Chandrasekhar; Yl, Ramachandra; Cp, Chandrappa (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objectives: The main aim is to elaborate a cost-effective and environmentally friendly synthesis of silver nanoparticles (AgNPs) by endophytic extracts isolated from Withania somnifera as a reducing and capping agent, which has proven antibacterial activity against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Klebsiella sp. Methods: Characterization of AgNPs was carried out employing ultraviolet-visible spectrophotometry, scanning electron microscopy (SEM), and X-ray diffraction studies (XRD). Antibacterial activity of AgNPs was conducted by disc diffusion method antimitotic activity was also evaluated by determining mitotic index in Allium cepa root tips. Results: Ultraviolet-visible spectroscopy was given a peak at 400 nm confirmed the AgNPs. The images of the SEM have confirmed the formation of AgNPs with an average size of 40 nm. XRD results were remarkable in confirmation of synthesized AgNPs with distinct XRD peaks at 2Î¸ values of 38, 44, 64, and 77 lattice planes were observed which indexed the facts of silver (111), (200), (220), and (311), respectively. The AgNPs showed effective antibacterial activity against tested microorganisms at 100 Î¼g/discs concentrations. A significant mitotic index (22.8Â±1.4b and 26.9Â±0.9b) was observed in A. cepa root tips at 10 mg/ml, 5 mg/ml concentration, respectively. Conclusion: It can be concluded that the endophytes of W. somnifera can be a good source for AgNP synthesis and showed a significant antimicrobial activity against tested microorganisms, especially E. coli followed by S. aureus and P. aeruginosa. Suggestive results were found in antimitotic activity which one of screening methods for development of anticancer drugs. An important outcome of our study will be the extension of value-added products for the industries of biomedical and nanotechnology based.